Aspirin does not prevent growth of vestibular schwannomas: A case‐control study. (6th February 2018) - MacKeith, Samuel; Wasson, Joseph; Baker, Charlotte; Guilfoyle, Matthew; John, Deepa; Donnelly, Neil; Mannion, Richard; Jefferies, Sarah; Axon, Patrick; Tysome, James R.
Abstract : Objectives/Hypothesis: To determine if aspirin intake is associated with reduced growth of vestibular schwannomas (VS). To determine the prevalence of contraindications to regular aspirin in patients with VS. Study Design: Retrospective, observational case‐control study. Methods: The study utilized a postal questionnaire and telephone interviews to determine aspirin exposure. Propensity score matching was used to control for age, sex, and tumor size. Cases were defined as patients with VS proven to have grown on serial magnetic resonance imaging (MRI). Controls were defined as patient with VS stable on serial MRI. Prevalence of regular aspirin use was compared in patients with growing VS versus stable VS. Absolute and relative contraindications to aspirin intake were recorded. Results: Six hundred fifty‐three patients with VS were contacted, and responses were received by 67% (220 cases and 217 controls). The mean tumor size was 11.3 mm (9.0 mm and 13.3 mm in controls and cases, respectively). Aspirin exposure was more common in stable VS than growing VS (22.1% vs. 17.3%). However, following matching to control for covariates, aspirin was not found to be associated with VS stability ( P  = .475). Multiple logistic regression (analysis of variance) found tumor size to be the only factor strongly associated with tumor growth ( P  < .0001). Ninety‐two percent of patients were able to take aspirin, with the majority being at low risk of complications from regular use. Conclusions: This study aimed to examine the relationship between aspirin intake and VS stability. In contrast to previous reports, after controlling for covariates, the findings do not demonstrate an association. Only tumor size at diagnosis appears predictive of risk of VS growth. Level of Evidence: 3b. Laryngoscope, 128:2139–2144, 2018